Analysis onThe Effect of Dap and NPK Fertilizers Applications on Broccoli Yield. - Bikorwomuhangi, Pastori (Kabale University, 2024)
The study investigated the effects of DAP (Diammonium phosphate) and NPK (Nitrogen-Phosphorus-Potassium) fertilizers on broccoli yield, aiming to provide insights into optimal fertilizer management strategies for enhancing crop yield. The study was based on three objectives: to assess the growth rate parameters of broccoli grown with DAP and NPK fertilizers, to determine the effects of DAP and NPK fertilizers on broccoli yield, and to propose recommendations for assessing the comparative effectiveness of DAP and NPK fertilizers in optimizing broccoli yield. Broccoli, a nutrient-demanding vegetable crop, was subjected to field trials where varying applications of DAP and NPK fertilizers were compared. The research measured key yield parameters including height, head size, and nutrient composition to evaluate the effect of each fertilizer type on overall crop yield and quality. Results indicated that both DAP and NPK fertilizers significantly influenced broccoli yield parameters. Specifically, plots treated with NPK showed enhanced height and larger head sizes of 3.5 kg compared to those treated with DAP with 2.5 kg or control groups with 1.7 kg. Findings revealed variations in nutrient uptake efficiency between the fertilizer types, with NPK-treated broccoli exhibiting a higher effect on yield production, the implications of fertilizer use were also assessed, emphasizing the need for balanced nutrient management to minimize environmental impact while maximizing agricultural productivity. The study recommended investigating how varying ratios or concentrations of these nutrients influence not only growth parameters like height and leaf count but also yield metrics such as head weight, investigating the efficiency of nutrient uptake by broccoli plants under different fertilizer treatments.